Pengabdian Masyarakat melalui Pemberdayaan Guru dan Masyarakat dalam Mengembangkan PAUD yang Berkualitas di Kota Ambon - Noya, Ferdinanda Sherly; Haumahu, Albertina Abetsi; Lokollo, Lamberthus Johannes (Universitas Pattimura, 2025)
Early childhood education is a crucial foundation for developing human resources from an early age. However, disparities in teacher competence and limited community involvement remain major challenges in achieving quality early education in Ambon City. This community service aimed to enhance teacher capacity and strengthen community roles through a locally based collaborative empowerment model. The method applied was Participatory Action Research (PAR), involving teachers, parents, and community leaders in cycles of planning, action, reflection, and evaluation. The findings revealed a significant improvement in teachers’ ability to design contextual learning (92%), greater parental engagement in school activities (87%), and the formation of sustainable inter-PAUD learning communities across five districts. The program produced an effective participatory empowerment model aligned with local characteristics and direct social impact. Its implication highlights that such collaboration can be replicated to support community-based education policies in other island regions.